Photocatalytic Performances of Dip-Coated Ag Doped TiO2 Thin Films - M. Alharbi; H. Althubyani; E. Alarfaj; D. Dastan; A. Timoumi; L. Tao; H. Albetran; Ş. Ţălu (Archives of Metallurgy and Materials)
In this study, dip coating technique is used to deposit titanium dioxide (TiO2) and silver (Ag)–doped–TiO2 nanocomposite thin films on glass substrates. The obtained films are typified using different characterization techniques such as X-ray diffraction (XRD), and UV–Vis-NIR spectroscopy. Films are also tested for environmental applications related to color degradation (methylene blue). The XRD analysis confirms that the prepared nanostructures are the anatase phase of titania. The crystal sizes of annealed Ag–TiO2 as well as TiO2 thin films have been summarized across the XRD pattern and are approximately 29±1 and 23±1 nm, respectively. Additionally, the energy bandgaps of the photocatalysts (Pure–TiO2 and Ag–TiO2) are found to be around 3.3 and 3.02 eV, respectively. The photocatalytic activity of TiO2 and Ag-doped TiO2 nanocomposite thin films is tested in the same initial concentrations of methylene blue in water (3×10−5 M). The photodegradation behavior of Ag–TiO2 (3% by weight) shows a good improvement against pure TiO2 for the concentrations of methylene blue in the pseudo-first order Langmuir-Hinshelwood (LH) model of the kinetics reaction. The global pseudo-first order reaction constant, k, for these concentrations goes from less than 1.4×10−3 min−1 for TiO2 films to 5.4×10−3 min−1,/p> for Ag–TiO2 films. This improvement is due to the incorporation of Ag, which increases the lifetime of the electrons and the separated holes, that decreases the rate of recombination (electron-hole) and which also generates reactive oxygen species. These features open the route to future applications for photocatalytic wastewater treatment and environmental remediation under solar irradiation.